(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Gastrointestinal parasitic infection is a serious threat to small ruminant industry. The control of helminth infection in goat are heavily relied on anthelmintic drugs. However, anthelmintic resistance has emerged as a big threat to the farmers and ruminant industry. Anthelmintic resistance against commonly used anthelmintic; Fenbendazole, was evaluated by using Faecal Egg Count Reduction Test (FECRT) of gastrointestinal (GI) parasites in a farm located in Setiu, Terengganu. GI parasites screening were carried out and a total of 28 animals with high parasites infection (EPG > 1000) were selected and divided into two groups (n= 14, Control vs Treatment). The Treatment group were administered with Fenbendazole (0.1ml/kg body weight) while Control group were leave untreated. Mean percentage reduction of FEC (95% upper and lower confidence limits) for the Treatment group are 32.75 (100 and -83) indicating resistant towards Fenbendazole treatment. The farm is recommended to use and alternate another group of anthelminthic drugs to treat their animals.